Multi-Functionalized Self-Assembling Peptides as Reproducible 3D Cell Culture Systems Enabling Differentiation and Survival of Various Human Neural Stem Cell Lines - Marchini, Amanda; Favoino, Chiara; Gelain, Fabrizio (Frontiers in Neuroscience, 2020)
Neural stem cells-based therapies have shown great potential for central nervous system regeneration, with three-dimensional (3D) culture systems representing a key technique for tissue engineering applications, as well as disease modelling and drug screenings. Self-assembling peptides (SAPs), providing biomimetic synthetic micro-environments regulating cellular functionality and tissue repair, constitute a suitable tool for the production of complex tissue-like structures in vitro. However, one of the most important drawbacks in 3D cultures, obtained via animal-derived substrates and serum-rich media, is the reproducibility and tunability of a standardized methodology capable to coax neural differentiation of different human cell lines. In this work we cultured four distinct human neural stem cell (hNSCs) lines in 3D synthetic multifunctionalized hydrogel (named HYDROSAP) for up to 6 weeks. 3D cultures of differentiating hNSCs exhibited a progressive differentiation and maturation over time. All hNSCs-derived neurons in 3D culture system exhibited randomly organized entangled networks with increasing expression of GABAergic and glutamatergic phenotypes and presence of cholinergic ones. Oligodendrocytes formed insulating myelin sheaths positive for myelin basic protein (MBP). In summary, results demonstrated a successfully standardized and reproducible 3D cell culture system for hNSC differentiation and maturation in serum-free conditions useful for future therapies.